Entrée dans des pratiques prostitutionnelles d’adolescentes nouvellement placées en foyer : analyse des interactions et facteurs favorisants - Héléna Frithmann; Nathalie Gavens (Sociétés et Jeunesses en Difficulté)
Prostitution is one of the main problems among the many risky behaviors of young admitted to placement institutions. However, this phenomenon, which has received little attention in the literature, is difficult to quantify and educators are not always equipped to find satisfactory solutions to these issues. In an attempt to shed light on these facts, we sought to understand whether the placement of newly placed adolescent girls in a shelter could impact their entry into prostitution. This article reports the observation of 10 adolescent girls (M = 16.2 years) placed in an educational center. We used a qualitative methodology based on direct observations and analyses of professional written documents. From the observations, it appears that placement in a child protection institution leads to a breaking point in the trajectories of these adolescents and to specific interactions between them and different actors. This systemic analysis shows that the environment, in the global sense, of the minors in care tends to favor their entry into prostitution. We were able to identify factors that can be considered as points of support and vigilance in in understanding this target group.